THE MECHANISM OF PROFESSIONAL JUDGMENT IN REALIZATION OF THE PRINCIPLES OF ACCOUNTING - S. Ponomareva; V. Mironenko (Вестник университета, 2017)
This article is devoted to a research of questions of professional judgment in realization of the principles of accounting, to formation of the mechanism of approaches to a regulation of activity of the accountant directly during the choice of options of conducting account. The qualified opinion of the expert has to be based on the ethical professional principles to receive financial statements which give the chance to its interested users to obtain qualitative and objective information on a condition of the enterprise.